The development of a Life Cycle Cost model for an offshore wind farm - Nordahl, Marcus (My University, 2011)
Not until recently most people have realised the severity of what all emissions are doing to mother earth. Today most countries are eco-friendly and see the pride in working towards a carbon independent community. This has led to an escalating growth of wind power energy and the development in this industry is growing like never before. To get as much out of the wind turbines as possible a lot of wind farms have lately been built offshore. The backside of this is that it is harder to predict the life cycle costs for the wind farm because of the lack of experience with offshore wind farms and the availability due to weather. The aim of this thesis is to develop a model that taking this into count when calculating the life cycle cost for a wind turbine. The model shows what kinds of costs and revenues that can be expected when building a wind farm. It also calculates the cost of energy per produced energy set over a lifetime. This is an accessible result that easily can be compared and since the results are different for each simulation it is presented in a distribution curve.
Keywords: Energi; Hållbar utveckling; Strömningsmekanik; Energy; Sustainable Development; Fluid mechanics